“BRASIL ACIMA DE TUDO E DEUS ACIMA DE TODOS”: O fator religioso na campanha presidencial de 2018 do candidato Jair Messias Bolsonaro em face do princípio da laicidade - Queiroz, Daniela Palhuca Do Nascimento (2020)
This research studies the religious factor in the 2018 presidential campaign of candidate Jair Messias Bolsonaro in the face of the constitutional principle of secularism in the Brazilian legal system. In view of the legal evolution of secularism in Brazilian constitutions and their relevance in the Democratic State of Law, we delimit our analysis to the parameters of the Federal Constitution of 1988. Supported by the theories of Law, Sociology of Religion, and Sciences of Religion, the study brings discusses the relationship between citizenship, freedom and secularism; religion, politics and voting. It is a broad analysis of evangelicals and politics in Brazil in the 21st century and focuses on the links between candidate Jair Messias Bolsonaro and Pentecostal leaders with an emphasis on the Assembly of God. It is part of our study, the religious representations in the pre-campaign and during the first and second round of the electoral period of 2018; voter support for the candidate who signals political agenda with religious military discourse; and the relevance of the evangelical religious vote as a lever and campaign strategy capable of influencing voters through evangelical leaders who verbalized their choices in the private and public space. The investigation is based on the review of relevant literature in the areas of knowledge mentioned above. It includes qualitative analysis of data collected systematically in selected communication vehicles. The religious factor in politics is studied under the concept of religious representations in the campaign of candidate Jair Bolsonaro. As for the method, it is a bibliographic research, based on books, magazines, articles, websites and legal norms.